Environmental characterization of a coffee processing workplace with obliterative bronchiolitis in former workers - Duling, Matthew G.; LeBouf, Ryan F.; Cox-Ganser, Jean M.; Kreiss, Kathleen; Martin, Stephen B.; Bailey, Rachel L. (Journal of occupational and environmental hygiene, 2016)
Obliterative bronchiolitis in five former coffee processing employees at a single workplace prompted an exposure study of current workers. Exposure characterization was performed by observing processes, assessing the ventilation system and pressure relationships, analyzing headspace of flavoring samples, and collecting and analyzing personal breathing zone and area air samples for diacetyl and 2,3-pentanedione vapors and total inhalable dust by work area and job title. Mean airborne concentrations were calculated using the minimum variance unbiased estimator of the arithmetic mean. Workers in the grinding/packaging area for unflavored coffee had the highest mean diacetyl exposures, with personal concentrations averaging 93 parts per billion (ppb). This area was under positive pressure with respect to flavored coffee production (mean personal diacetyl levels of 80 ppb). The 2,3-pentanedione exposures were highest in the flavoring room with mean personal exposures of 122 ppb, followed by exposures in the unflavored coffee grinding/packaging area (53 ppb). Peak 15-min airborne concentrations of 14,300 ppb diacetyl and 13,800 ppb 2,3-pentanedione were measured at a small open hatch in the lid of a hopper containing ground unflavored coffee on the mezzanine over the grinding/packaging area. Three out of the four bulk coffee flavorings tested had at least a factor of two higher 2,3-pentanedione than diacetyl headspace measurements. At a coffee processing facility producing both unflavored and flavored coffee, we found the grinding and packaging of unflavored coffee generate simultaneous exposures to diacetyl and 2,3-pentanedione that were well in excess of the NIOSH proposed RELs and similar in magnitude to those in the areas using a flavoring substitute for diacetyl. These findings require physicians to be alert for obliterative bronchiolitis and employers, government, and public health consultants to assess the similarities and differences across the industry to motivate preventive intervention where indicated by exposures above the proposed RELs for diacetyl and 2,3-pentanedione.